A Rare Case of Plasma Cell Gingivitis with Cheilitis - Yashodeep Chauhan; Shaleen Khetarpal; Madhu Singh Ratre; Manish Varma (Case Reports in Dentistry)
Background. Plasma cell gingivitis (PCG) is a rare condition of the gingiva, characterized histopathologically by infiltration of plasma cells in connective tissue. Hypersensitivity reaction due to antigen is considered as primary etiological factor. Case Presentation. The present case is of an 18-year-old male patient suffering from gingival enlargement along with cheilitis. Histopathological and immunohistochemistry of tissue revealed lesion as plasma cell gingivitis. After gingivectomy, the follow up of the patient was done for 8 months. Gradual reduction of lip swelling was observed after gingivectomy during subsequent visits. Conclusion. Early diagnosis is essential as plasma cell gingivitis has similar pathologic changes seen clinically as in leukemia, multiple myeloma, discoid lupus erythematosus, atrophic lichen planus, desquamative gingivitis, or cicatricial pemphigoid which must be differentiated through hematologic examination.